Optimal points of operational parameters of sulphuric acid, phosphic acid, and ammonia production process - Jati, Gahara Mahadyatmika; Wibowo, Wahyu (International Journal Labs, 2023)
PT Petrokimia Gresik is the most complete fertilizer producer in Indonesia and produces various types of fertilizers. NPK is a fertilizer that contains nitrogen (N) to make plants greener, phosphorus (P) to stimulate root growth, and potassium (K) to make plants more upright and sturdy. This study aims to determine the optimum value of using sulfuric acid, phosphoric acid, and ammonia so as to obtain the best value in producing NPK fertilizer. This research method uses quantitative descriptive research methods by collecting secondary data, namely the use of sulfuric acid, phosphoric acid, and ammonia for a period of 1 year. Researchers use multiple regression analysis to determine whether or not there is an influence between the three variables to be studied, then the data is processed and analyzed to determine whether the regression model used is feasible to use before finally calculating the optimal point of NPK fertilizer production. The stages of data optimization in this study are the data collection stage, the data processing stage (descriptive data, parameter estimation, regression model), the data analysis and interpretation stage (F test, t test, IIDN assumption test for determining the optimum point), and the conclusion and suggestion stage. This study concluded that obtaining the optimum point for the amount of NPK fertilizer production can be done by regulating the use of phosphoric acid at 211.91 tons, Sulphuric acid at 844,099 tons, and ammonia at 308,055 tons. Total fertilizer production achieved with the use of optimum parameters amounted to 2085.38 tons.